Copper foam effectively improves the thermal performance of graphene-aerogel composite phase-change materials for thermal storage. (July 2022) - Pan, Changyu; He, Ping; Wu, Jiang; Chen, Naichao; Wei, Jie; Xu, Tianhong; Shi, Enqi; Wang, Aofei; Jia, Haodong
Abstract: Phase-change heat-storage technology is capable of solving problems associated with the mismatch between the supply and demand of heat energy. In this work, meso -erythritol/graphene-aerogel (mE/GA) and meso -erythritol/graphene-aerogel/copper-foam (mE/GA/CF) composite phase-change materials (PCMs) were prepared by self-reduction and vacuum-impregnation methods. Both experimental and simulation data show that, compared to mE/GA, the composite PCM augmented with CF more-effectively encapsulates the graphene-aerogel composite phase-change material (GACPCM), improving its shape stability and thermal properties, including its thermal stability, subcooling performance, enthalpy, and thermal conductivity. mE/GA/CF exhibits a thermal conductivity of 2.705 W m −1 K −1, which is nearly 13-times that of a common graphene-aerogel thermal-storage unit (GATSU), thus improving the usability of GATSU in the energy-conversion and storage field. Highlights: Erythritol/graphene-aerogel (mE/GA) composite phase-change thermal storage unit was prepared. mE/GA/copper-foam (mE/GA/CF) composite phase-change thermal storage unit was prepared. CF effectively encapsulates and stabilizes the mE/GA. mE/GA/CF is more thermally conductive (2.705 W m −1 K −1 ) than pure mE or mE/GA. Numerical simulation was used to corroborate the improved thermal performance of mE/GA/CF.